Genome-wide Integration Study of Circulating miRNAs and Peripheral Whole-Blood mRNAs of Male Acute Ischemic Stroke Patients. (1st June 2018) - Xue, Yang; Yin, Pengqi; Li, Guozhong; Zhong, Di
Highlights: Bioinformatic integration of the circulating miRNA and peripheral whole-blood mRNA networks expressed during male AIS. Twenty-four mRNAs in peripheral whole blood overlapped with the regulation of seven circulating miRNAs. Common up-regulation of circulating miRNAs and targeted mRNAs were observed under AIS stress. The overlapped mRNAs were associated with platelet degranulation and immune response. The overlapped mRNAs were associated with phagosome biology and Staphylococcus aureus infection. Abstract: Several circulating microRNAs (miRNAs) have been proved to serve as stable biomarkers in blood for acute ischemic stroke (AIS). However, the functions of these biomarkers remain elusive. By conducting the integration analysis of circulating miRNAs and peripheral whole-blood mRNAs using bioinformatics methods, we explored the biological role of these circulating markers in peripheral whole blood at the genome-wide level. Stroke-related circulating miRNA profile data (GSE86291) and peripheral whole-blood mRNA expression data (GSE16561) were collected from the Gene Expression Omnibus (GEO) datasets. We selected male patients to avoid any gender differences in stroke pathology. Male stroke-related miRNAs (M-miRNAs) and mRNAs (M-mRNAs) were detected using GEO2R. Nine M-miRNAs (five up- and four down-regulated) were applied to TargetScan to predict the possible target mRNAs. Next, we intersected these targets with the M-mRNAs (38 up- and three down-regulated) to obtain the male stroke-related overlapped mRNAs (Mo-mRNAs). Finally, we analyzed biological functions of Mo-mRNAs using the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG), and constructed networks among the Mo-mRNAs, overlapped M-miRNAs (Mo-miRNAs), and their functions. The Mo-mRNAs were enriched in functions such as platelet degranulation, immune response, and pathways associated with phagosome biology and Staphylococcus aureus infection. This study provides an integrated view of interactions among circulating miRNAs and peripheral whole-blood mRNAs involved in the pathophysiological processes of male AIS.